A new seismicity catalogue of the eastern Alps using the temporary Swath-D network - L. J. Hofman; J. Kummerow; S. Cesca (Solid Earth, 2023)
We present a new, consistently processed seismicity catalogue for the eastern and southern Alps based on the temporary dense Swath-D monitoring network. The final catalogue contains 6053 earthquakes for the time period 2017–2019 and has a magnitude of completeness of −1.0 ML. The smallest detected and located events have a magnitude of −1.7 ML. Aimed at the low to moderate seismicity in the study region, we have developed a multi-stage, mostly automatic workflow that combines a priori information from local catalogues and waveform-based event detection, subsequent efficient GPU-based (GPU: graphics processing unit) event search by template matching, P and S arrival time pick refinement, and location in a regional 3-D velocity model.